Traceback and Anonymity - Wang, Xinyuan; Reeves, Douglas; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This brief systematically examines the trackback problem and its interaction with low-latency anonymous communication. First, it provides an overview of the common techniques a network-based attack may use to hide its origin and identity. Then the authors explore the MIX-based anonymity and the building blocks of low-latency anonymous communication. Later chapters offer a comprehensive study of the timing attacks on low-latency anonymous communication, and analyze the fundamental limitations of low-latency anonymous communication from the perspective of timing-based covert channel. Suitable for professionals and researchers, Traceback and Anonymity is a close look at a key aspect of cyber security studies. Advanced-level students interested in cyber security techniques or networking will also find the content valuable.
Keywords: Computer science; Computer Applications